Blood pressure‐related differences in brain health between young African Americans and Caucasian Americans. Issue 6 (26th March 2021) - Won, Junyeon; Ranadive, Sushant M.; Callow, Daniel D.; Chen, Shuo; Carson Smith, J.
Abstract: Background: Although there are moderating effects of race on blood pressure (BP) and brain health in older adults, it is currently unknown if these race‐related differences in cardiovascular and associated brain function are also present in younger adults. The purpose of this study was to investigate the interaction between race and BP on brain health in younger African (AA) and Caucasian Americans (CA). Methods: We studied 971 younger adults (29.1 ± 3.5 years; 180 AAs and 791 CAs) who volunteered to participate in the Human Connectome Project. Cognitive composite scores, brain volume, and cortical thickness using MRI were cross‐sectionally assessed. ANCOVA was used to examine interactions between race and mean arterial pressure (MAP) on cognitive test scores and brain structure. Results: After controlling for age, sex, education, and BMI, there were significant Race × MAP interaction effects on cognitive composite scores and cortical thickness. Among AAs but not CAs, as MAP increased, both global cognitive performance and entorhinal cortex (ERC) thickness decreased. Conclusions: MAP was an important moderator of racial differences in cognitive performance and ERC thickness. Our findings suggest that young AAs may carry a greater hypertension‐associated risk for cognitive brain health deficit. Interventions that address early signs of hypertension in AAs are needed to determine if the racial disparities in BP‐related brain health in late adulthood can be reduced. Abstract : Our findings provide evidence that there are significant negative associations between mean arterial pressure and cognitive composite scores and cortical thickness in younger African Americans that were not observed in their Caucasian counterparts. Among African Americans, but not Caucasian Americans, as mean arterial pressure increased, both global cognitive performance and entorhinal cortex thickness decreased. Our findings suggest that young African Americans may carry a greater hypertension‐associated risk for poor cognitive brain health.